The Implementation of Organic Snake Gourd Cultivation to Increase Income in Pondok Village - Rohmawati Nur Fathonah; Soleh Hasan Wahid (Jurnal Pengabdian Masyarakat, 2023)
Purpose: This research focuses on transitioning snake gourd cultivation in Pondok Babadan Village from conventional to organic methods using polybag media to enhance production quality and quantity. Method: Utilizing the ABCD (Asset Based Community Development) approach, this study involves training on organic bitter gourd cultivation in polybag containers, emphasizing knowledge dissemination, polybag utilization, and cost-effective bitter gourd seeds. Practical Applications: Implementing organic farming techniques and polybag containers can optimize land use, reduce chemical pesticide reliance, and promote healthier vegetable production. These practices offer income potential for Pondok Babadan Village's MSMEs and support sustainable agriculture. Conclusion: Transitioning to organic snake gourd cultivation using polybag media offers improved quality, increased yield, cost savings, and eco-friendly practices. This research provides valuable insights for small-scale farmers and contributes to sustainable agriculture in the region.